Calcium channel blockers do not protect against saturated fatty acid-induced ER stress and apoptosis in human pancreatic β-cells - Šrámek, Jan; Němcová, Vlasta; Kovář, Jan (Nutrition & metabolism, 2021)
It was evidenced that saturated fatty acids (FAs) have a detrimental effect on pancreatic β-cells function and survival, leading to endoplasmic reticulum (ER) calcium release, ER stress, and apoptosis. In the present study, we have tested the effect of three calcium influx inhibitors, i.e., diazoxide, nifedipine, and verapamil, on the apoptosis-inducing effect of saturated stearic acid (SA) in the human pancreatic β-cell lines NES2Y and 1.1B4. We have demonstrated that the application of all three calcium influx inhibitors tested has no inhibitory effect on SA-induced ER stress and apoptosis in both tested cell lines. Moreover, these inhibitors have pro-apoptotic potential per se at higher concentrations. Interestingly, these findings are in contradiction with those obtained with rodent cell lines and islets. Thus our data obtained with human β-cell lines suggest that the prospective usage of calcium channel blockers for prevention and therapy of type 2 diabetes mellitus, developed with the contribution of the saturated FA-induced apoptosis of β-cells, seems rather unlikely.
Keywords: Pancreatic β-cells; NES2Y; Diazoxide; Calcium influx; Nifedipine; 1.1B4; Type 2 diabetes mellitus; Verapamil; Fatty acids; Apoptosis